A cultura escolar da educação física no EJA : O paradoxo entre a ruptura com a noção de atividade e a falta da prática corporal - Pich, Santiago (Educación Física y Ciencia.)
This paper is the result of a research based on the school culture concept, which object is the specific school culture of the physical education (PE) within a school for youth and adults situated in Curitiba - PR. Methodologically we followed the principles and concepts of the ethnomethodology, that led us to a long immersion in the research field. The main results of the research show the relevance of the teacher identity for constituting the school culture of the PE, as well the paradox resulting of a mere theoretical approach: on the one hand this school culture show us the importance of the disruption with the PE's tradition based on the notion of "activity", and on the other hand reveal the necessity of the body experience as a fundament to build a theoretical construct